The Science of Heat - Harris, Nic (NewYork Cambridge University, 2014)
What does the word hot mean ? From the Sahara Desert to heatstroke, from temperature to emotions, learn how heat affects our world.
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Pre-Intermediate Level; Sciences